Management of Primary Education for Ethnic Chinese Children during the Dutch Colonial Period 1900-1920 - Sumardi (Basic and Applied Education Research Journal, 2023)
The management of primary education for ethnic Chinese children during the Dutch colonial period 1900-1920, to analyze the primary education of ethnic Chinese children (HCS) by the Dutch Colonial Government in 1900-1920. This research method uses five steps: Topic Selection, Heuristics, Verification, Interpretation, and Historiography. The results showed that the establishment of primary education for ethnic Chinese was due to the large number of immigrant children from China who did not get the proper attention to go to school. Then the Chinese community association Tiong Hoa Hwee Koan (THHK) began to think about the education of its descendants and established Primary Education. Apart from this, Chinese children who attended ELS could also not follow the lessons properly. This reason strengthened the colonial government to build a particular school for ethnic Chinese children, namely Hollandsch Chineesche School (HCS).